Attitudes and perceptions about breastfeeding among female and male informal workers in India and South Africa - C. Horwood; A. Surie; L. Haskins; S. Luthuli; R. Hinton; A. Chowdhury; N. Rollins (BMC, 2020)
Abstract Background Worldwide, over 740 million women make their living in the informal economy and therefore lack formal employment benefits, such as maternity leave, that can improve infant feeding practices. Returning to work is one of the biggest challenges women face to maintaining breastfeeding. This study aimed to explore attitudes and perceptions towards breastfeeding in the informal work environment among male and female informal workers. Methods The study used a qualitative research design. Purposive and snowball sampling was employed. Focus group discussions (FGDs) were conducted among men and women working in different types of informal jobs, in India and South Africa. Data was analysed using a thematic approach and the framework method. Results Between March and July 2017, 14 FGDs were conducted in South Africa and nine in India. Most women were knowledgeable about the benefits of breastfeeding and reported initiating breastfeeding. However, pressures of family responsibilities and household financial obligations frequently forced mothers to return to work soon after childbirth. Upon return to work many mothers changed their infant feeding practices, adding breastmilk substitutes like formula milk, buffalo milk, and non-nutritive fluids like Rooibos tea. Some mothers expressed breastmilk to feed the infant while working but many mothers raised concerns about expressed breastmilk becoming 'spoilt'. Breastfeeding in the workplace was challenging as the work environment was described as unsafe and unhygienic for breastfeeding. Mothers also described being unable to complete work tasks while caring for an infant. In contrast, the flexibility of informal work allowed some mothers to successfully balance competing priorities of childcare and work. Sociocultural challenges influenced breastfeeding practices. For example, men in both countries expressed mixed views about breastfeeding. Breastfeeding was perceived as beneficial for both mother and child, however it was culturally unacceptable for women to breastfeed in public. This affected working mothers' ability to breastfeed outside the home and contributed to a lack of respect for women who chose to breastfeed in the workplace. Conclusion Mothers working in the informal sector face multiple challenges to maintaining breastfeeding. Interventions are required to support feeding and childcare if global nutrition and development goals are to be met.